Hybrid Materials and Polymer Electrolytes for Electrochromic Device Applications - Thakur, Vijay Kumar; Ding, Guoqiang; Ma, Jan; Lee, Pooi See; Lu, Xuehong (Advanced materials (Weinheim), 2012)
Electrochromic (EC) materials and polymer electrolytes are the most imperative and active components in an electrochromic device (ECD). EC materials are able to reversibly change their light absorption properties in a certain wavelength range via redox reactions stimulated by low direct current (dc) potentials of the order of a fraction of volts to a few volts. The redox switching may result in a change in color of the EC materials owing to the generation of new or changes in absorption band in visible region, infrared or even microwave region. In ECDs the electrochromic layers need to be incorporated with supportive components such as electrical contacts and ion conducting electrolytes. The electrolytes play an indispensable role as the prime ionic conduction medium between the electrodes of the EC materials. The expected applications of the electrochromism in numerous fields such as reflective‐type display and smart windows/mirrors make these materials of prime importance. In this article we have reviewed several examples from our research work as well as from other researchers’ work, describing the recent advancements on the materials that exhibit visible electrochromism and polymer electrolytes for electrochromic devices. The first part of the review is centered on nanostructured inorganic and conjugated polymer‐based organic‐inorganic hybrid EC materials. The emphasis has been to correlate the structures, morphologies and interfacial interactions of the EC materials to their electronic and ionic properties that influence the EC properties with unique advantages. The second part illustrates the perspectives of polymer electrolytes in electrochromic applications with emphasis on poly (ethylene oxide) (PEO), poly (methyl methacrylate) (PMMA) and polyvinylidene difluoride (PVDF) based polymer electrolytes. The requirements and approaches to optimize the formulation of electrolytes for feasible electrochromic devices have been delineated. Electrochromic (EC) materials and polymer electrolytes are the most imperative components in an electrochromic device (ECD). The present review article focuses on the recent advancements on the nanostructured inorganic and conjugated polymer‐based organic–inorganic hybrid EC materials. The review also highlights the progress on polymer electrolytes for electrochromic devices as platforms for practical applications.